Yes, I can say no : a parent's guide to assertiveness training for children - Smith, Manuel J., 1934- (New York : Arbor House, 1986)
Presents a program designed to teach assertive social skills to children between the ages of seven and seventeen, enabling them to cope with peer pressure, resist drugs and alcohol, and improve academic performance.
Bibliography: p. 313.
13 31
Keywords: Interpersonal relations in children; Child psychology; Parenting; Child rearing; Assertiveness in children